EDUCATIONAL ENVIRONMENT OF PRESCHOOL EDUCATION: GENESIS AND CONTENT - Koshil, Oksana (Educological discourse, 2017)
The problem of educational environment and its influence on the effectiveness of education is one of the highest priorities in modern pedagogical science and practice. Analysis of the source base has led to the conclusion that modern pedagogical space is polyspectra scientists to the concept of "educational environment" as phenomenon that directly or indirectly affects the development of its subjects, and the concept "educational environment" is multidimensional, reflected in different theoretical models, determined by a variety of definitions and interpretations. The analysis of the source base made it possible to conclude that in the modern pedagogical space there is an interest of scientists in the polyaspect concept of "educational environment" as a phenomenon that directly or indirectly influences the development of its subjects, and the concept "educational environment" is multidimensional, reflected in different theoretical models, is determined by a variety of definitions and interpretations. In the broadest sense, the educational environment is understood by the environment, which consists of a set of natural, material, social factors that directly or indirectly influence the personality. It was found out that qualitative psychological and pedagogical support of the process of child growth is determined by the quality of the created educational conditions, main among which is the educational environment of preschool educational institution, which provides optimum development of the individual. Based on the scientific analysis of educational environment of preschool educational institution is considered as an integral factor of psychological and personal development of the child, which plays a crucial role in ensuring its potential of implementation of congenital programs, opportunities, self-determination and self-actualization. In the article the essence of the concepts «environment», «educational environment», «educational environment of preschool educational institutions» has been shown; theoretical approaches to the definition of the essence of the educational environment of preschool educational institutions have been observed; the ways of providing the effective development of the individual in a pre-school educational institution have been described.